EMPLOYEE PERFORMANCE IS REVIEWED FROM WORK ENVIRONMENT, LEADERSHIP, REMUNERATION, AND MUTATION AT PRATAMA SURAKARTA TAX SERVICE OFFICE - FX. Wahyu Rahmanto; Istiatin Istiatin; Sudarwati Sudarwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to (1) Test and analyze the influence of the work environment on employee performance in KPP Pratama Surakarta, (2) Test and analyze the influence of leadership on employee performance in KPP Pratama Surakarta, (3) Test and analyze the effect of remuneration on employee performance in KPP Pratama Surakarta, (4) Test and analyze the effect of mutations on employee performance in KPP Pratama Surakarta. This type of quantitative research. The population is all employees in the Tax Service Office of Pratama Surakarta, which amounts to 129 people. The sampling technique used in this study is purposive sampling which is a sampling technique with specific considerations. The research samples taken were as many as 32 employees of KPP Pratama Surakarta. Data retrieval techniques using questionnaires. Data analysis techniques are multiple linear regressions.The results showed that (1) Work environment variables have a significant impact on the performance of KPP Pratama Surakarta employees, (2) Leadership variables have a significant effect on the performance of KPP Pratama Surakarta employees, (3) Remuneration variables have a significant effect on the performance of KPP Pratama Surakarta employees, (4) Mutation variables have a significant impact on the performance of KPP Pratama Surakarta employees, (5) Work environment variables, leadership, remuneration, and mutations simult significant impact on the performance of KPP Pratama Surakarta employees. Keyword : work environment, leadership, remuneration, mutation, performance